2019
DOI: 10.1002/jca.21760
|View full text |Cite
|
Sign up to set email alerts
|

A modified PLASMIC score including the lactate dehydrogenase/the upper limit of normal ratio more accurately identifies Chinese thrombotic thrombocytopenic purpura patients than the original PLASMIC score

Abstract: Background: The PLASMIC score was recently published to aid in the early identification of thrombotic thrombocytopenic purpura (TTP) patients. This study aims to evaluate whether this score is suitable for Chinese suspected TTP patients and find the utility of patients' other characteristics in predicting severe ADAMTS13 deficiency. Methods: We retrospectively studied a Chinese cohort of 38 consecutive hospitalized patients with suspected TTP, ADAMTS13 test results, and other clinical data from September 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 16 publications
3
32
0
Order By: Relevance
“…The cause and significance of the elevation of D‐dimers in patients with HIV‐associated TTP also requires further investigation. 13 , 31 Based on the results of the study, the authors support the addition of the LDH/upper‐limit‐of‐normal ratio to the PLASMIC score for improved diagnostic accuracy and to guide urgent, but appropriate, institution of therapeutic plasma exchange (TPE) as was proposed by Zhao et al 36 …”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The cause and significance of the elevation of D‐dimers in patients with HIV‐associated TTP also requires further investigation. 13 , 31 Based on the results of the study, the authors support the addition of the LDH/upper‐limit‐of‐normal ratio to the PLASMIC score for improved diagnostic accuracy and to guide urgent, but appropriate, institution of therapeutic plasma exchange (TPE) as was proposed by Zhao et al 36 …”
Section: Discussionmentioning
confidence: 77%
“…The PLASMIC score may therefore not have sufficient specificity to delineate between HIV‐TTP and HIV‐DIC in all cases and inclusion of the LDH/upper‐limit‐of‐normal ratio is likely to improve the specificity and accuracy. Zhao et al 36 also demonstrated that inclusion of the LDH/upper‐limit of‐normal ratio improved the accuracy of the PLASMIC score in identifying patients who suffered from TTP. Increased schistocyte count was also a distinguishing feature between the TTP and DIC cohort but this parameter is poorly standardized with considerable inter‐observer variability since it often relies on the subjective methodology of light microscopy and manual counting of cells 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Tiscia et al demonstrated the good diagnostic performance of the PLASMIC score in a cohort from Southern Italy ( 19 ). Another study of a small Chinese cohort reported that a modified PLASMIC score, which included lactate dehydrogenase in addition to the original seven items of the PLASMIC scoring system, might be more suitable for identifying patients with ADAMTS13 deficiency ( 31 ). To the best of our knowledge, few studies with larger cohorts have validated the PLASMIC score as a new prediction tool and this is the first study to verify the ability of the PLASMIC score to predict TTP risk in an East Asian cohort.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4]6 To our knowledge this is the first publication to describe the use of these particular modifications, although other modifications to the PLASMIC score have been described in the literature. 3,7,8 We created Mod 3 due to the non-specific nature of some features included in the PLASMIC score. In the patient group with an ADAMTS13 activity of more than 10% in this study, three of the seven features (no active cancer, no transplant history, and INR < 1.5) were each present in 79%-83% of patients.…”
Section: Performance Of the Plasmic Score Is Improved With A Positive...mentioning
confidence: 99%
“…One hundred and twenty-four of the patients at Peking University have been reported previously. 7 All patients provided informed consent, according to the procedures of the institutional review board of each centre and in accordance with the Declaration of Helsinki. The cut-off date for follow-up was 28 February 2021.…”
Section: Su Pp Ort I Ng I N For M At Ionmentioning
confidence: 99%